Development of Eu3+ doped boro-tellurite oxyfluoride glass and their Judd-Ofelt analysis for red laser gain medium application. (2019) - Yuliantini, L.; Djamal, M.; Hidayat, R.; Yasaka, P.; Kaewkhao, J.; Boonin, K.
Abstract: This paper investigated the physical, optical, luminescence and radiative properties of Eu 3+ doped borotellurite oxyfluoride glass with composition (30-x)TeO2 -30B2 O3 -10ZnF2 -30BaO-xEu2 O3 where x are 0.05, 0.10, 0.50, 1.00 and 1.50 mol%. The glass samples were fabricated by melt and quenching method. The physical and optical properties were investigated from density, molar volume and refractive index. Meanwhile absorption spectra that show several transitions in the ultraviolet to near infrared region interpret the optical properties of the glass sample. The emission spectra of glass sample were measured under excited λex = 394 nm. The highest peak of emission spectra occurs in 1.5 mol% of Eu2 O3 due to 5 D0 → 7 F2 transition centered at 613 nm. The emission intensity was increased by the addition of Eu2 O3 from 0.05 mol% to 1.5 mol%. In addition, Judd-Ofelt (JO) theory was used to define the radiative properties and lasing potential of the glass sample. The value of JO parameter Ω2, Ω4, Ω6 was calculated and compared with literatures. Other radiative properties including experimental ( fexp ) and calculated ( fcal ) oscillator strengths, stimulated emission cross-sections (σ), radiative transition probability ( AR ), experimental and calculated branching ratios ( βR ) of glass sample were determined and discussed in term of red laser gain medium application.